Financial incentives and the timing of retirement: evidence from Switzerland - Barbara Hanel; Regina T. Riphahn (Institute for the Study of Labor (IZA), 2006)
We use reforms in the Swiss public retirement system to identify the responsiveness of retirement timing to financial incentives. A permanent reduction of retirement benefits by 3.4 percent induces more than 70 percent of females to postpone their retirement. The responsiveness of male workers, who undergo a different treatment, is lower.
urn:nbn:de:101:1-20080509221
Keywords: 330